A visit to another class? Working-class graduates entering university and the graduate labour market in Finland. Issue 2 (4th March 2023) - Haltia, Nina; Isopahkala-Bouret, Ulpukka
ABSTRACT: Working-class students often face more challenges in securing graduate-level jobs than their middle-class peers. This paper applies the concept of boundary crossing in studying the experience of Finnish business graduates from a working-class background ( n = 27) and asks what types of boundaries they have faced and how they have managed them on their pathway through and after university studies. We identify three major boundaries: getting the actual study place, learning to be a student in university and graduating and getting a job in the graduate labour market. Our findings indicate that successful transitions are possible, as the Finnish higher education system enables them in many ways. However, successful boundary work demands socialising to the norms and values of the new social field as well as renewed relationships with one's social background. This paper discusses the implications of these findings for the development of inclusive policies and practices.